Price / earnings ratio as a measure of stock prices: consumer product sector on Main Board / Nurlian Ezdiani Abdullah - Abdullah, Nurlian Ezdiani (2002)
Standard ratios are used to measure an organization's performance relative to other representative organizations in a particular industry. This study was carried out to understand the relationships between P/E ratios and stock prices of the companies listed on the Main Board. Since there are 102 companies listed on the Main Board, this study only focus and analyze the sample of 15 companies, which have been listed for 5 years (1997 to 2001). Data were obtained from companies' website, annual companies handbook published by KLSE and websites http://www.klse.com.my and http:/www.klse-ris.com.my. Methodology used was P/E ratio in order to understand its relationships with stock prices. The results obtained show that there are significant relationships between P/E ratios and stock prices for certain listed companies. From this study, it was found out that about 60% of the companies listed on the Main Board have significant relationships between P/E ratios and stock prices.